Aerodynamical Measurements of the Small Indian kite (Milvus migrans govinda) - Sharma, Aarti; Dubal, S. C. (Indian Journal of Veterinary Anatomy, 2017)
The aerodynamic characters viz. body weight, body length, wing span, wing area, wing load and aspect ratio were measured in the present study. The mean value of body weight, body length, wing span, wing area and wing load of the small Indian kite were 682.67 ± 12.98 g, 54.50 ± 0.43 cm, 136.67 ± 2.74 cm, 2532.90 ±104.82 cm2 and 0.269 ± 0.01 gcm-2respectively. Aspect ratio is a simple measure of the shape of the wing. All anatomical and aerodynamical parameters concluded that the small Indian kite was gliding and soaring bird.